Implementation of Character Education through Learning Pancasila and Citizenship Education in Sungguminasa 1 State Junior High School, Gowa Regency - Andi Sugiati; Jumiati Nur; Nurannisah Anwar (Universitas of Muhammadiyah Makassar, 2021)
Abstract. The main problem in this study aims to describe the implementation of character education through learning Pancasila and Citizenship Education at Sungguminasa State Junior High School 1, Gowa Regency. This type of research is a qualitative descriptive study. The data collection techniques used were interviews, observation, and documentation. Data analysis techniques using data reduction steps, data presentation, and drawing conclusions. The results showed that the implementation of character education through learning Pancasila and Citizenship Education in the learning process of Pancasila and Citizenship Education in class VIII.B of the State Junior High School 1 Sungguminasa, Gowa Regency has been implemented by teachers through planning. In learning planning, there is a character value contained in self-development activities including routine, spontaneous and exemplary activities, while learning activities in the Learning Implementation Plan are in Core competencies and Basic Competencies (KD). There are several supporting factors experienced by teachers in learning Pancasila and Citizenship Education, namely, students create comfortable and conducive classes, teachers provide motivation and understanding of the importance of character values, provide role models, advice, rewards and punishments, and teachers create interesting learning and fun through the learning methods Student Active Learning and Collaborative Learning, while the inhibiting factors experienced by teachers in learning Pancasila and Citizenship Education, namely, Not conducive to learning Pancasila and Citizenship Education with student rest periods that make learning Pancasila and Citizenship education hampered and student learning enthusiasm decreases. , and the inadequacy of printed books for students which triggers a lack of interest in reading in students is due to the lack of printed books and this also has an impact on students when they test.Keywords: Character Education, Learning, Pancasila and Citizenship EducationAbstrak. Masalah utama dalam penelitian ini bertujuan mendeskripsikan implementasi pendidikan karakter melalui pembelajaran Pendidikan Pancasila dan Kewarganegaraan di Sekolah Menengah Pertama Negeri 1 Sungguminasa Kabupaten Gowa. Jenis penelitian ini merupakan penelitian deskriptif kualitatif. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan dokumentasi. Teknik analisis data dengan menggunakan langkah-langkah reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian diperoleh bahwa implementasi pendidikan karakter melalui pembelajaran Pendidikan Pancasila dan Kewarganegaraan dalam proses pembelajaran Pendidikan Pancasila dan Kewarganegaraan kelas VIII.B Sekolah Menengah Pertama Negeri 1 Sungguminasa Kabupaten Gowa telah dilaksanakan oleh guru melalui perencanaan. Dalam perencanaan pembelajaran adalah adanya nilai karakter yang termuat kegiatan pengembangan diri meliputi kegiatan rutin, spontan dan keteladanan sedangkan kegiatan belajar dalam Rencana Pelaksanaan Pembelajaran yaitu pada kompetensi Inti dan Kompetensi Dasar (KD). Terdapat beberapa faktor pendukung yang dialami guru dalam pembelajaran Pendidikan Pancasila dan Kewarganegaraan yaitu, siswa menciptakan kelas yang nyaman dan kondusif, guru memberikan motivasi dan pemahaman tentang pentingnya nilai-nilai karakter, memberikan teladan, nasihat, penghargaan dan hukuman, dan Guru menciptakan pembelajaran yang menarik dan menyenangkan melalui metode pembelajaran Student Active Learning dan Collaborative Learning, sedangkan faktor penghambat yang dialami guru dalam pembelajaran Pendidikan Pancasila dan Kewarganegaraan yaitu, Tidak kondusifnya pembelajaran Pendidikan Pancasila dan Kewarganegaraan dengan waktu istirahat siswa yang membuat pembelajaran Pendidikan Pancasila dan Kewarganegaraan terhambat dan semangat belajar siswa menurun, dan tidak memadainya buku cetak pada siswa yang memicu kurangnya minat baca pada siswa diakibatkan kurangnya buku cetak dan ini juga berdampak pada siswa ketika ulangan.Kata Kunci: Pendidikan Karakter, Pembelajaran, Pendidikan Pancasila dan Kewarganegaraan.